Docking studies and molecular dynamics simulation of Ipomoea batatas L. leaves compounds as lipoxygenase (LOX) inhibitor - Yeni Yeni; Supandi Supandi; Lusi P Dwita; Suswandari Suswandari; Maizatul S Shaharun; Nonni S Sambudi (Wolters Kluwer Medknow Publications, 2020)
Background: Inflammatory mediators produced by cyclooxygenase (COX) and lipoxygenase (LOX) pathways are responsible for many human diseases, such as cancer, arthritis, and neurological disorders. Flavonoid-containing plants, such as Ipomoea batatas leaves, have shown potential anti-inflammatory activity. Objectives: This study aimed to predict the actions of 10 compounds in I. batatas leaves, which are YGM-0a [cyanidin 3-0-sophoroside-5-0-glucosede], YGM-0f [cyanidin 3-O-(2-0-(6-0-(E)-p-coumaroyl-β-D-glucopyranosyl)-β-D-glucopyranoside)-5-0-β-D-glucopyranoside], YGM-1a [cyanidin 3-(6,6'-caffeylp-hydroxybenzoylsophoroside) -5-glucoside], YGM-1b [cyanidin 3-(6,6'-dicaffeylsophor-oside)-5-glucoside], YGM-2 [cyanidin 3-(6-caffeylsophoroside)-5-glucoside], YGM-3 [cyanidin 3-(6,6'-caffeyl-ferulylsophoroside)-5-glucoside], YGM-4b [peonidin 3-(6,6'-dicaffeylsophoroside)-5- glucoside], YGM-5a [peonidin 3-(6,6'-caffeylphydroxybenzo-ylsophoroside)-5-gluco-side], YGM-5b [cyanidin 3-6-caffeylsophoroside)-5-glucosede], and YGM-6 [peonidin 3-(6,6'-caffeylferulylsophoroside)-5-glucoside] as LOX inhibitors, and also predict the stability of ligand-LOX complex. Materials and Methods: The compounds were screened through docking studies using PLANTS. Also, the molecular dynamics simulation was conducted using GROMACS at 310K. Results: The results showed that the most significant binding affinity toward LOX was shown by YGM-0a and YGM-0a, and the LOX complex in molecular dynamics simulation showed stability for 20 ns. Conclusion: Based on Docking Studies and Molecular Dynamics Simulation of I. Batatas Leaves compounds, YGM-0a was shown to be the most probable LOX inhibitor.